Service-learning sebagai Strategi untuk Mempromosikan Global Citizenship di Indonesia: Service-learning as a Strategy to Promote Global Citizenship in Indonesia - Yusuf Faisal Ali; Yayuk Hidayah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
The problem behind this research is service-learning usefulness as a strategy to promote global citizenship at universities in Indonesia. The methodology used in this research is a qualitative type of phenomenology. The research subjects were students involved in the Student Executive Board or Badan Eksekutif Mahasiswa (BEM) organization from eight different campuses in the Special Region of Yogyakarta or Daerah Istimewa Yogyakarta (DIY). The research results show two findings, 1) service-learning in student organizations can promote global citizenship values, and 2) service-learning in student organizations can improve industrial skills. Thus, this study concluded that student organizations in higher education could be a place to promote global citizenship and improve industrial revolution 4.0 skills among students. Therefore, the recommendation in this study is for further researchers to research by emphasizing learning outcomes that focus on the level of numbers and readiness to face the industrial revolution, which includes the ability to adopt values ??and nature as Indonesian people and as citizens of the world.